Pengaruh Pembangunan Industri Kelapa Terhadap Pemanfaatan Lahan Di Desa Kayutanyo Kecamatan Luwuk Timur Kabupaten Banggai - Muh Alfian Pradana Putra; Jufriadi Jufriadi (Fakultas Teknik Universitas Bosowa, 2020)
This study aims to determine what factors influence the impact of industrial activities against changed of land use in Kayutanyo Village, East Luwuk District, Banggai Regency. As well as how much land use change occurred in Kayutanyo Village, East Luwuk District, Banggai Regency. The government of Banggai Regency, this research can be used as input on the relationship between industrial development and land use. As well as how much land use change occurred in Kayutanyo Village, East Luwuk District, Banggai Regency. For the government of Banggai Regency.There are four variables used, (1) conversion of agricultural land functions, (2) conversion of residential land functions, (3) Environmental Pollution (4) Land Price. The analytical method used is in the form of chi-square analysis, then a contingency test is used in drawing conclusions, which is followed by a Likert scale scoring system as a parameter to determine the magnitude of the relationship between X and Y variables. Furthermore, to find out how much land use change has occurred during the last 5 years, work process using ArcGis software application version 10.6.1. The overlay process technique is carried out by overlapping the 2016 land use map and the 2020 land use map.The results of this study indicate that the variables have an influence on industrial activity in Kayutanyo Village. And it shows that some areas in Kayutanyo Village, Luwuk Timur Subdistrict, Banggai Regency have experienced changes, which are from built land to built-up land.